Solid polymer electrolyte with flexible interface, and preparation method and application thereof
By using cationic lignin as filler, a solid polymer electrolyte with a flexible interface is prepared, which solves the problems of large interface impedance, poor mechanical properties and low ionic conductivity of the polymer solid electrolyte in the prior art, and significantly improves the electrochemical performance of the battery.
Patent Information
- Application Number
- CN202510121595.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-04-29
AI Technical Summary
The existing polymer solid electrolytes have large interface impedance, poor mechanical properties and low ionic conductivity, especially in room temperature and low temperature environments, resulting in poor electrochemical performance of the battery.
Cationic lignin is used as filler and mixed with ionic liquid, electrolyte salt and polyethylene oxide to prepare solid polymer electrolyte with flexible interface by vacuum drying.
It significantly improves the interface flexibility and ionic conductivity of the solid electrolyte, enhances the cyclic stability and capacity retention of the battery, and improves the electrochemical performance.
Smart Images

Figure CN119905653A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of solid polymer electrolytes, and more specifically, relates to a solid polymer electrolyte with a flexible interface, a preparation method thereof, and an application thereof. Background Art
[0002] With the rapid development of energy, lithium-ion batteries have been widely used in new energy electric vehicles, aerospace and other fields. At the same time, although sodium-ion batteries are not as good as lithium-ion batteries in terms of specific capacity, they have emerged in the field of energy storage due to their good cycle stability. Especially in the past two years, many scientific researchers have focused on sodium-ion batteries, which are rich in resources, lower in cost, have stable electrochemical properties and higher in safety performance. It is expected that sodium-ion batteries will be widely used in energy storage batteries, base station backup power supplies, low-speed four-wheel vehicles, electric two-wheel vehicles and other fields, forming a complementary pattern with lithium batteries.
[0003] Electrolyte is an indispensable key component in battery materials and plays a vital role in the performance of battery materials. Currently, the most widely used is liquid electrolyte, but the flammability, explosiveness, and dendrite growth of liquid electrolytes have greatly caused safety hazards to batteries. Based on this, solid electrolytes have ushered in new opportunities and new challenges, which can greatly improve the safety performance of batteries and effectively reduce problems such as electrolyte decomposition, leakage, and dendrite growth.
[0004] Common solid electrolytes are inorganic sulfide solid electrolytes and organic polymer solid electrolytes. Sulfide solid electrolytes have significant advantages in energy density and rate performance, but their high price and environmental pollution have hindered the application of such electrolytes to a certain extent. In contrast, polymer solid electrolytes are low in cost and highly designable, so they have been favored by many researchers. However, the most prominent problems of polymer solid electrolytes are large interface impedance, poor mechanical properties, and low ionic conductivity, especially at room temperature and low temperature. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of this application is to provide a method for constructing a flexible interface of a solid electrolyte and its application. By constructing a polymer solid electrolyte with a flexible interface, it aims to solve the technical problems of the prior art such as large interface impedance, poor mechanical properties, low ionic conductivity and poor electrochemical performance of the corresponding battery of the polymer solid electrolyte.
[0006] To achieve the above objectives, in a first aspect, the present application provides a method for preparing a solid polymer electrolyte with a flexible interface, comprising the following steps: (1) mixing and dispersing cationized lignin, an ionic liquid and an electrolyte salt in an organic solvent to obtain a dispersion; the electrolyte salt is a lithium salt or a sodium salt used to prepare an electrolyte; (2) In an anhydrous and oxygen-free environment, the dispersion liquid of step (1) is mixed with polyethylene oxide to obtain a mixed liquid, the mixed liquid is cast into a film, and then vacuum dried to obtain a flexible solid polymer electrolyte.
[0007] Preferably, the lignin in step (1) is one or more of softwood kraft lignin, hardwood kraft lignin, enzymatic lignin, and thermoplastic lignin.
[0008] Preferably, the preparation method of the cationized lignin in step (1) comprises the following steps: dissolving lignin in an aqueous solution of sodium hydroxide, then mixing with epoxy ammonium salt, heating the reaction under an inert atmosphere to cationize the lignin, and dialyzing, exchanging water, and drying the mixed solution obtained by the reaction to obtain the cationized lignin.
[0009] Preferably, in step (1), the mass ratio of the cationized lignin, the ionic liquid, the electrolyte salt and the organic solvent is 1:(1-40):(0.2-10):(20-1500).
[0010] Preferably, in step (2), the mass ratio of the dispersion to polyethylene oxide is 1:1 to 1:10; and / or, The organic solvent in step (1) is one or more of acetonitrile, tetrahydrofuran and N-methylpyrrolidone; and / or, The vacuum drying temperature is 40 to 60°C, and the drying time is 12 to 36 hours.
[0011] According to another aspect of the present invention, a solid polymer electrolyte with a flexible interface prepared by the preparation method is provided.
[0012] According to another aspect of the present invention, there is provided a use of the solid polymer electrolyte as a solid electrolyte for a lithium / sodium ion battery.
[0013] In general, the above technical solutions conceived by this application have the following beneficial effects compared with the prior art: (1) The present invention uses cationized lignin as a filler and composites it with ionic liquid, electrolyte salt and PEO polymer to prepare a solid polymer electrolyte. Experiments have found that compared with the active fillers commonly used in the prior art, the solid electrolyte prepared by the present invention using lignin filler has a high degree of interface flexibility, and the capacity retention rate of the assembled battery after long cycles is significantly better than that of the solid polymer electrolyte prepared by conventional active fillers.
[0014] (2) The solid polymer electrolyte provided by the present invention has a flexible interface that can be restored after bending or being compressed. When used as a solid electrolyte for lithium-ion or sodium-ion batteries, it can enhance grain boundary bonding and inhibit the growth of dendrites. It can also increase the contact area between the electrolyte and the electrode surface, provide more active sites for the reaction, and thus improve the ionic conductivity. The method for constructing a flexible interface of a solid electrolyte provided by the present invention is applicable to the synthesis of a series of polymer solid electrolytes, has low cost, strong universality and broad application prospects, and is easier to industrialize.
[0015] (3) The present invention provides a method for constructing a flexible interface of a polymer solid electrolyte, and obtains a solid electrolyte with a flexible interface. In a preferred embodiment, the ionic conductivity is 0.278 mS / cm. After the battery is assembled, it is charged and discharged at a rate of 0.1C. The first cycle charge and discharge specific capacities measured at room temperature are 168.95 mAh / g and 157.93 mAh / g, respectively. The first cycle efficiency is 93.48%. The capacity retention rate after 100 cycles is 96.68%, which is significantly better than the polymer solid electrolytes in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of the lignin cationization process in an embodiment of the present invention.
[0017] Figure 2 The surface morphology and cross-sectional thickness SEM image of the polymer solid electrolyte prepared in Example 1 of the present invention.
[0018] Figure 3 Nanoindentation curves of the polymer solid electrolytes prepared in Example 1 and Example 13 of the present invention and Comparative Examples 1 and Comparative Examples 13.
[0019] Figure 4 Graphs showing the ionic conductivity of polymer solid electrolytes prepared in some embodiments and comparative examples of the present invention.
[0020] Figure 5 The electrochemical performance diagrams of polymer solid electrolytes prepared in some embodiments and comparative examples of the present invention are shown in FIG. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0022] Due to the low ionic conductivity of PEO itself, the existing technology usually uses active filler LGPS (Li 10 GeP2S 12) or NZSP (Na3Zr2Si2PO 12 ) is mixed with PEO, ionic liquid and electrolyte salt to prepare solid polymer electrolyte. The active filler itself contains lithium ions or sodium ions, which can participate in the transport of ions, so it is beneficial to improve the conductivity of the solid polymer electrolyte. However, experiments have found that although the solid polymer electrolyte prepared with active fillers has a high conductivity, the long-term cycle performance of the battery is not very good, and the battery capacity decreases rapidly during the cycle. For this reason, the present invention attempts to use cationized lignin to replace the active filler. Experiments have found that cationized lignin as a filler can also disperse electrolyte salts, ionic liquids and PEO well, and because hydrogen bonds are formed between the cationized lignin, PEO and ionic liquids, the flexibility of the interface of the prepared solid polymer electrolyte is improved, and ultimately the capacity retention rate of the battery is significantly improved.
[0023] The present invention provides a method for preparing a solid polymer electrolyte with a flexible interface, comprising the following steps: (1) mixing and dispersing cationized lignin, ionic liquid, and electrolyte salt in an organic solvent to obtain a dispersion; the electrolyte salt is a lithium salt or a sodium salt used to prepare an electrolyte; (2) In an anhydrous and oxygen-free environment, the dispersion liquid of step (1) is mixed with polyethylene oxide magnetic force to obtain a mixed liquid, the mixed liquid is cast into a film and then vacuum dried to obtain a flexible solid polymer electrolyte.
[0024] The lignin used in the embodiments of the present invention can be lignin itself or a raw material containing lignin, which can be prepared by itself or directly purchased. In some embodiments, the lignin in step (1) is one or more of softwood kraft lignin, hardwood kraft lignin, enzymatic lignin, and thermoplastic lignin.
[0025] In some embodiments, the preparation method of the cationized lignin in step (1) comprises the following steps: dissolving lignin in an aqueous solution of sodium hydroxide, then mixing in epoxy ammonium salt, heating the reaction under an inert atmosphere to cationize the lignin, the epoxy ammonium salt ring opening and dehydration condensation reaction with the hydroxyl groups in the lignin molecular structure, dialyzing the mixed solution obtained by the reaction, changing water, and drying to obtain the cationized lignin. The purpose of cationization of lignin is to make the lignin molecules charged, so as to facilitate the subsequent ion exchange with ionic liquid, PEO and electrolyte lithium / sodium salt, and promote the transport of lithium ions / sodium ions in the entire system.
[0026] In some embodiments, the epoxy ammonium salt is epoxypropyl trimethyl ammonium chloride (GTAC) and / or glycidyl trimethyl ammonium chloride (GTMAC). Taking the epoxy ammonium salt as GTAC as an example, the schematic diagram of its cationization process is as follows: Figure 1 shown.
[0027] In some embodiments, the mass ratio of the lignin to the epoxy ammonium salt is 1:1~10:1, and the molar concentration of the sodium hydroxide solution is 0.1~1.0 mol / L; the heating reaction is water bath heating, the water bath temperature is 40~80°C, the reaction time is 1~10 h, and after the reaction is completed, it is cooled to room temperature and stirred for 12~48 h; dialysis is performed using a semipermeable membrane, the semipermeable membrane dialysis time is 12~72 h, the cationized lignin obtained by dialysis separation has a molecular weight of 1~10 kDa, and the drying is freeze-drying, and the freeze-drying time is 12~36 h.
[0028] In some embodiments, the mass ratio of the cationized lignin, ionic liquid, electrolyte salt and organic solvent in step (1) is 1: (1 ~ 40): (0.2 ~ 10): (20 ~ 1500).
[0029] In a preferred embodiment, the ionic liquid is one or more of 1-ethyl-3-methylimidazolium dicyanamide (EmimDCA), 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EmimTFSI) and 1-ethyl-3-methylimidazolium tetrafluoroborate (EmimBF4).
[0030] In some embodiments, the electrolyte lithium salt is one or more of sodium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorooxalatoborate LiDFOB, lithium difluorophosphate LiDFP, and lithium bis(fluorosulfonyl)imide LiFSI; the electrolyte sodium salt is one or more of sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), sodium difluorooxalatoborate NaDFOB, sodium difluorophosphate NaDFP, and sodium bis(fluorosulfonyl)imide NaFSI.
[0031] In some embodiments, step (1) uses ultrasonic mixing and dispersion, and the ultrasonic dispersion time is 10 to 90 minutes. Step (2) uses magnetic stirring for mixing.
[0032] In some embodiments, the mass ratio of the dispersion to polyethylene oxide in step (2) is 1:1-1:10; the organic solvent in step (1) is one or more of acetonitrile, tetrahydrofuran and N-methylpyrrolidone (NMP); the vacuum drying temperature is 40-60°C, and the drying time is 12-36 h.
[0033] The solid polymer electrolyte with a flexible interface prepared by the present invention can be used as a solid electrolyte for lithium ion or sodium ion batteries. The solid polymer electrolyte with a flexible interface provided by the present invention can not only enhance the grain boundary bonding by utilizing the elastic properties of the flexible interface, but also effectively inhibit the growth of dendrites, and can also make the electrolyte fully contact with the electrode material, thereby improving the ionic conductivity of the battery material and the electrochemical performance of the battery when used as a lithium / sodium ion battery electrolyte.
[0034] The embodiments of the present invention are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and processes are given, but the protection scope of the present invention is not limited to the following embodiments. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0035] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0036] The process parameters without specific conditions in the following examples are usually based on conventional conditions.
[0037] The following are examples and comparative examples: Example 1 A method for constructing a solid electrolyte flexible interface and application thereof, comprising the following steps: (1) Weigh 5.0 g of lignin filler (coniferous wood kraft lignin, purchased from Jinan Scott Experimental Equipment Co., Ltd.), dissolve it in 50 mL of freshly prepared 0.5 mol / L sodium hydroxide solution, and stir it thoroughly. Slowly add 2.5 g of glycidyl trimethylammonium chloride (GTAC) dropwise, place in a 60 °C water bath under nitrogen atmosphere, stir and react for 5 h, cool to room temperature and continue stirring for 12 h to obtain a uniform mixed solution. Use a semipermeable membrane to dialyze the mixed solution for 72 h, change the water regularly, and freeze-dry for 20 h to obtain cationic lignin with a molecular weight of 4 kDa. (2) Weigh 0.096 g of the cationized lignin obtained in step (1), 0.1800 g of the ionic liquid EmimDCA and 0.036 g of the lithium salt LiTFSI, add them to 5 g of anhydrous acetonitrile, and disperse them by ultrasonication for 40 min to obtain a uniformly dispersed mixed solution; (3) The mixed solution of step (2) was transferred into a glove box, 0.200 g was weighed, 0.5 g of PEO polymer was added to the mixed solution, and magnetic stirring was performed to obtain a uniformly dispersed mixed solution. A small amount of the dispersion was cast into a film and placed in a vacuum oven at 45 °C for 20 h to obtain a composite solid electrolyte membrane.
[0038] (4) The prepared flexible solid electrolyte was assembled into an all-solid-state battery with the positive electrode material lithium iron phosphate and the negative electrode lithium sheet, and its electrochemical performance was measured.
[0039] (5) The prepared flexible solid electrolyte and stainless steel were assembled into a symmetrical battery and the AC impedance was tested according to the formula σ = The ionic conductivity was calculated.
[0040] The amount of lignin in Example 1 was adjusted to 0.0048 g, 0.024 g, 0.048 g, 0.072 g, 0.12 g and 0.144 g, and the other conditions were the same as in Example 1, namely, Example 2, Example 3, Example 4, Example 5, Example 6 and Example 7.
[0041] The ionic liquid EmimDCA in Example 1 was respectively treated with EmimTFSI, EmimBF4, PP 13 BF4 is used as the substitute, and other conditions are the same as those in Example 1, namely, Example 8, Example 9 and Example 10.
[0042] The organic solvent in Example 1 was replaced with THF, and other conditions were the same as Example 1, which is Example 11.
[0043] The polymer PEO in Example 1 is replaced with PVDF, and other conditions are the same as Example 1, which is Example 12.
[0044] The lithium salt LiTFSI in Example 1 is replaced with the sodium salt NaTFSI, and other conditions are the same as Example 1, which is Example 13.
[0045] Comparative Example 1 A method for constructing a solid electrolyte flexible interface and application thereof, comprising the following steps: (1) Weigh 0.096 g of LGPS filler (purchased from Hefei Kejing Material Technology Co., Ltd.), 0.1800 g of ionic liquid EmimDCA and 0.036 g of lithium salt LiTFSI, add them to 5 g of anhydrous acetonitrile, and disperse them by ultrasonic for 40 min to obtain a uniformly dispersed mixed solution; (3) The mixed solution of step (2) was transferred into a glove box, 0.200 g was weighed, 0.5 g of PEO polymer was added to the mixed solution, and magnetic stirring was performed to obtain a uniformly dispersed mixed solution. A small amount of the dispersion was cast into a film and placed in a vacuum oven at 45 °C for 20 h to obtain a composite solid electrolyte membrane.
[0046] (3) The prepared flexible solid electrolyte was assembled into an all-solid-state battery with the positive electrode material lithium iron phosphate and the negative electrode lithium sheet, and its electrochemical performance was measured.
[0047] (4) The prepared flexible solid electrolyte and stainless steel were assembled into a symmetrical battery and the AC impedance was tested according to the formula σ = The ionic conductivity was calculated.
[0048] The amount of LGPS in Comparative Example 1 was adjusted to 0.0048 g, 0.024 g, 0.048 g, 0.072 g, 0.12 g and 0.144 g, and the other conditions were the same as Comparative Example 1, namely Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5, Comparative Example 6 and Comparative Example 7.
[0049] The ionic liquid EmimDCA in Comparative Example 1 was respectively treated with EmimTFSI, EmimBF4, PP 13 BF4 is used as the substitute, and other conditions are the same as those in Comparative Example 1, namely Comparative Example 8, Comparative Example 9 and Comparative Example 10.
[0050] The organic solvent in Comparative Example 1 was replaced with THF, and other conditions were the same as those in Comparative Example 1, which was Comparative Example 11.
[0051] Comparative Example 12 is obtained by replacing the polymer PEO in Comparative Example 1 with PVDF, while other conditions are the same as those in Comparative Example 1.
[0052] Comparative Example 13 A method for constructing a solid electrolyte flexible interface and application thereof, comprising the following steps: (1) Weigh 0.096 g of NZSP filler, 0.1800 g of ionic liquid EmimDCA and 0.036 g of sodium salt NaTFSI, add them to 5 g of anhydrous acetonitrile, and disperse them by ultrasonic for 40 min to obtain a uniformly dispersed mixed solution; (3) The mixed solution of step (2) was transferred into a glove box, 0.200 g was weighed, 0.5 g of PEO polymer was added to the mixed solution, and magnetic stirring was performed to obtain a uniformly dispersed mixed solution. A small amount of the dispersion was cast into a film and placed in a vacuum oven at 45 °C for 20 h to obtain a composite solid electrolyte membrane.
[0053] (3) The prepared flexible solid electrolyte was assembled into an all-solid-state battery with the positive electrode material lithium iron phosphate and the negative electrode lithium sheet, and its electrochemical performance was measured.
[0054] (4) The prepared flexible solid electrolyte and stainless steel were assembled into a symmetrical battery and the AC impedance was tested according to the formula σ = The ionic conductivity was calculated.
[0055] Comparative Example 14 The rest is the same as Example 1, except that the ionic liquid EmimDCA is not added in step (2).
[0056] The surface morphology and cross-sectional thickness of the polymer solid electrolyte prepared in Example 1 were analyzed using a scanning electron microscope. Figure 1 SEM plan and cross-sectional images are shown. Figure 2 It can be seen that the prepared polymer solid electrolyte has a smooth surface and a cross-sectional thickness of 54.26 μm.
[0057] The polymer solid electrolytes prepared in Example 1, Comparative Example 1, Example 13 and Comparative Example 13 were subjected to nanoindentation curve measurement using a nanoindenter from Wuhan University. Figure 3 Content. From Figure 3 It can be clearly seen that when the four prepared polymer solid electrolyte materials are under the same load pressure, the elasticity of Example 1 and Example 13 is significantly better than that of Comparative Example 1 and Comparative Example 13. Among them, Example 1 has the best nanoindentation elasticity, and loses its elasticity only when the indentation depth reaches 1136.37 nm, while Example 13 also shows excellent elasticity, with an indentation depth of 889.09 nm; while Comparative Example 1 and Comparative Example 13, when the indentation depths are 650.15 nm and 598.91 nm respectively, have lost their rebound ability. This result shows that lignin filler is more conducive to the preparation of solid electrolytes with flexible interfaces. The nanoindentation experiment can better simulate the flexibility of the test electrolyte. If a deep indentation is made but it can still rebound, it means that the electrolyte has a high degree of flexibility.
[0058] The prepared polymer solid electrolyte was tested for impedance using an electrochemical workstation. Figure 4 Content. From Figure 4It can be clearly seen that the impedance of the lithium salt system obtained in Example 1 and Comparative Example 1 is not significantly different. It can be seen that although the lignin filler is an inert filler, it may be because it constructs a solid electrolyte with a flexible interface, which effectively inhibits the growth of lithium dendrites and also increases the contact area between the electrolyte and the electrode surface, providing more reactive sites, so that it has an impedance that is not much different from the active filler LGPS. At the same time, it can also be seen from Example 13 and Comparative Example 13 that the solid electrolyte constructed by lignin in the sodium salt system also has a smaller impedance. Therefore, it can be said that whether it is a lithium ion battery or a sodium ion battery, lignin can be used as a filler to construct a solid electrolyte with a flexible interface. In addition, the ionic conductivity of each embodiment and comparative example was calculated and listed in Table 1.
[0059] Table 1 Ionic conductivity of polymer solid electrolytes in lithium / sodium ion batteries
[0060] As mentioned above, because the active filler itself contains lithium ions and sodium ions, the solid polymer electrolyte prepared by the active filler in the comparative example will be higher, but from the data, the conductivity of the solid polymer electrolyte prepared by the inert lignin filler in the embodiment of the present invention is not much different from that of the comparative example, and the conductivity of the polymer electrolyte in Example 13 is even higher than that of the comparative example 13. Comparative Example 14 does not introduce ionic liquid. As can be seen from Table 1, the solid polymer electrolyte prepared by it is significantly lower.
[0061] It can also be seen from Table 1 that when lignin is used as filler, different ionic liquids, organic solvents, polymers and their dosages also have a great influence on the ionic conductivity of the solid electrolyte. Among them, the polymer solid electrolytes prepared by using lignin filler in Example 1 and Example 13 have higher ionic conductivity, which are 0.278 mS / cm and 0.198 mS / cm respectively; while the ionic conductivity corresponding to the active filler in Comparative Example 1 and Comparative Example 13 is 0.292 mS / cm and 0.151 mS / cm. Analyzing these two sets of data, it is not difficult to find that this result is consistent with Figure 3 The conclusions obtained are consistent with those of the previous paper and will not be repeated here.
[0062] Based on the research on improving ionic conductivity, the present invention also tests the electrochemical performance of the prepared polymer solid electrolyte after assembling it into a battery. The results show that Figure 5 As shown. Figure 5It can be clearly seen that the battery assembled with the polymer solid electrolyte prepared with cationized lignin as filler has better cycle stability. After 100 cycles at a rate of 0.1C, the discharge specific capacities of Example 1 and Example 13 were 157.93 mAh / g and 133.93 mAh / g, respectively, and the capacity retention rates were as high as 93.48% and 92.21%, respectively; while those of Comparative Example 1 and Comparative Example 13 were 167.71 mAh / g and 108.68 mAh / g, and the capacity retention rates were 86.76% and 79.67%, respectively. It can be seen that the battery capacity attenuation of the battery assembled with the solid polymer electrolyte prepared with lignin filler after cyclic use is significantly lower than that of the battery corresponding to the electrolyte prepared with active filler, which may still be attributed to the fact that the polymer solid electrolyte prepared with lignin has a flexible interface, which greatly improves the ionic conductivity and electrochemical performance.
[0063] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a solid polymer electrolyte with a flexible interface, characterized in that: The steps include: (1) mixing and dispersing cationized lignin, an ionic liquid and an electrolyte salt in an organic solvent to obtain a dispersion; the electrolyte salt is a lithium salt or a sodium salt used to prepare an electrolyte; (2) In an anhydrous and oxygen-free environment, the dispersion liquid of step (1) is mixed with polyethylene oxide to obtain a mixed liquid, the mixed liquid is cast into a film, and then vacuum dried to obtain a flexible solid polymer electrolyte.
2. The preparation method according to claim 1, characterized in that The lignin in step (1) is one or more of softwood kraft lignin, hardwood kraft lignin, enzymatic lignin, and thermoplastic lignin.
3. The preparation method according to claim 1, characterized in that: Step (1) The method for preparing the cationized lignin comprises the following steps: dissolving lignin in an aqueous solution of sodium hydroxide, then mixing with epoxy ammonium salt, heating the reaction under an inert atmosphere to cationize the lignin, and dialyzing, exchanging water, and drying the mixed solution obtained by the reaction to obtain the cationized lignin.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the cationized lignin, ionic liquid, electrolyte salt and organic solvent in step (1) is 1: (1 ~ 40): (0.2 ~ 10): (20 ~ 1500).
5. The preparation method according to claim 1, characterized in that: The ionic liquid is one or more of 1-ethyl-3-methylimidazolium dicyandiamide, 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide and 1-ethyl-3-methylimidazolium tetrafluoroborate.
6. The preparation method according to claim 1, characterized in that: The electrolyte lithium salt is one or more of sodium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate and lithium bis(fluorosulfonyl)imide; The electrolyte sodium salt is one or more of sodium bis(trifluoromethanesulfonyl)imide, sodium difluorooxalatoborate, sodium difluorophosphate and sodium bis(fluorosulfonyl)imide.
7. The preparation method according to claim 1, characterized in that: Step (1) uses ultrasonic mixing and dispersion, and the ultrasonic dispersion time is 10 to 90 minutes; and / or, The organic solvent in step (1) is one or more of acetonitrile, tetrahydrofuran and N-methylpyrrolidone.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the dispersion to the polyethylene oxide in step (2) is 1:1 to 1:10; and / or, The vacuum drying temperature is 40 to 60°C, and the drying time is 12 to 36 hours.
9. A solid polymer electrolyte with a flexible interface prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the solid polymer electrolyte according to claim 9 as a solid electrolyte for lithium / sodium ion batteries.